MANAJEMEN STRATEGIS KEPALA SEKOLAH DALAM UPAYA MENARIK MINAT CALON PESERTA DIDIK DI SMPIT AR-RIDHO PALEMBANG - Irmayani, Herni; Wardiah, Dessy (Graduate Program Magister Manajemen Pendidikan, 2017)
This research aimed at identifying the strategic management of the principal in attracting prospective learners in Islamic Intergrity Secondary School Ar-Ridho Palembang, how the implementation in attracting prospective students in Islamic Intergrity Secondary School Ar-Ridho Palembang, Evaluation and follow-up of principal strategy in attracting candidate students in Islamic Intergrity Secondary School Ar-Ridho Palembang, This research was qualitative. The subjects of this research were principal, committee of Studentsâ Admission and some parents. The instruments were interviews and observations. Data analysis used Miles and Huberman model. The result of the research was that during the two years of Studentsâ Admission implementation, the headmaster and Studentsâ Admission committee experienced difficulties in cooperation with the foundation, especially on Studentsâ Admission funds. Technically all the preparations include the formation of the committee, the determination of activity, budget, schedule, determining the location of the activity, the target of the activity, and the determination of the material in the activity already programmed. The media used to remember the minimal cost is limited based information from parents whose children are learning in Secondary School Ar-Ridho Palembang Ar-Ridho. Evaluation was done in the closing meeting of Studentsâ Admission, the things are evaluated include the match between the number of learners with the target capacity, the weaknesses was on the method or committee.Â Keywords: Strategic Management, Headmaster, Studentsâ Interest, SDIT Ar-Ridho